Parameters of viscous flow in dilute solutions of polyalkyl glycol ethers in secondary alcohols - Aznarez, Silvia (2011)
Densities and viscosities were measured for the binary dilute mixtures of triethylene glycol monomethyl ether (TRIEGMME) in 2-alcohols (2-propanol (2-PR), 2-butanol (2-BU), and 2-pentanol (2-PE)) and tetraethylene glycol dimethyl ether (TEGDME) in 2-pentanol, at temperatures from 288.15 K to 318.15 K and in 0 ≤ x2 ≤ 0.10 mol fraction range of the polyalkyl glycol ethers. The values of the dynamic viscosity in the TRIEGMME + 2-PR systems are more viscous than pure solvent at the work temperatures. The Jones–Dole B coefficients and βG interaction parameters for viscous flow values were calculated and explain the behavior observed. The partial molar volumes at infinite dilution of solute in 2-alkanols were calculated by the parameters of viscous flow obtained in dilute solutions polyalkyl glycol ethers in 2-alkanols. The values have been compared with the values of partial molar volume at infinite dilution obtained by density measurement for both solutes in the 2-propanol, 2-butanol, and 2-pentanol.